POLYESTER BATTING FOR CLOTHING AND MITTEN INSULATING LAYERS - Madnick, Herman (1966)
The report describes the feasibility of using a flame-bonded polyester insulating layer to replace a stitch-bonded insulating material for clothing and mitten environmental layers. Substitution of this material would reduce the weight of the end product and lower the ultimate cost to the government because it would require fewer fabrication processes.